Evaluation of the Food Contact Suitability of Aged Bio-Nanocomposite Materials Dedicated to Food Packaging Applications - Anaïs Lajarrige; Nathalie Gontard; Sébastien Gaucel; Stéphane Peyron (Applied Sciences, 2020)
Nanocomposite materials based on bio-polyesters (PBSA and PHBV) have been evaluated for their suitability for food contact according to the recommendations defined for non-biodegradable plastic materials, and subsequently, according to accelerated aging treatment. On the basis of the limited number of material/migrant/food simulant combinations studied here, the test for migration, using food simulants, appeared directly applicable to testing such materials which are not considered humidity-sensitive materials. Considering the only compliance criterion that must be met by the materials in contact, the materials submitted to the aging processing are not of safety concern and the incorporation of nanoclays in aged biodegradable materials does not interfere with their inertial properties in a dramatic way. At the molecular scale, the UV irradiation proved to induce an increase in the degree of crystallinity, resulting in a modification of transport properties of both packaging materials. The values of overall migration and specific migration were reduced without decreasing the diffusion coefficients of the target additives. The UV treatment and the addition of nanoparticles, therefore, seem to jointly promote the retention of organic compounds in the materials by increasing their affinity for packaging material.